2013
DOI: 10.1371/journal.pntd.0002412
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Dengue Shock Syndrome: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe pathogenesis of dengue shock syndrome (DSS, grade 3 and 4) is not yet completely understood. Several factors are reportedly associated with DSS, a more severe form of dengue infection that reportedly causes 50 times higher mortality compared to that of dengue patients without DSS. However, the results from these reports remain inconclusive. To better understand the epidemiology, clinical manifestation, and pathogenesis of DSS for development of new therapy, we systematically reviewed and performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
167
6
27

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(225 citation statements)
references
References 58 publications
25
167
6
27
Order By: Relevance
“…13,15,21,22,26 The DENV-2 was recently found to be significantly associated with DSS in several countries. 27 However, all serotypes could lead to severe forms and death 1 ; among the deaths observed during the study period, one notes that half were attributed to cardiovascular-associated disease, diabetes, sickle cell disease, or nosocomial infections contracted in intensive care. The existence of a chronic disease that has been decompensated by viral infection increases the risk of death in dengue.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,21,22,26 The DENV-2 was recently found to be significantly associated with DSS in several countries. 27 However, all serotypes could lead to severe forms and death 1 ; among the deaths observed during the study period, one notes that half were attributed to cardiovascular-associated disease, diabetes, sickle cell disease, or nosocomial infections contracted in intensive care. The existence of a chronic disease that has been decompensated by viral infection increases the risk of death in dengue.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies assessing the factors associated with severe dengue or DSS. (24,25) The WHO proposed a list of warning signs, such as abdominal pain, persistent vomiting, mucosal bleed, and lethargy, for predicting severe dengue and the need for strict observation. However, a study by Thanachartwet et al found that the sensitivity and specificity of the 2009 WHO warning signs (except the presence of clinical fluid accumulation) were too low for identifying severe dengue at admission.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados pueden explicarse por un cambio en el patrón de enfermedad que se caracteriza por hiperendemicidad, la circulación simultánea de varios serotipos del virus del dengue (DENV 1, DENV 2, DENV 3 y DENV 4) y la falta de conciencia de la población en cuanto a medidas de prevención o de formación del profesional de salud en el reconocimiento oportuno de las formas graves 3,37 . Es importante que cuanto antes se identifique un factor de riesgo de muerte, mayor es la posibilidad de introducir intervenciones terapéuticas adecuadas para evitar la misma, lo que impone la necesidad de conocerlos 44,45 . Los pacientes con infecciones secundarias por el virus del dengue tienen un mayor riesgo de desarrollar FHD/SSD 44,45,47 .…”
Section: Discussionunclassified